Tuberculous dacryoadenitis in a child - Chakraborti, C; Biswas, R; Mondal, M; Muknopadhya, U; Datta, J (Nepalese Journal of Ophthalmology, 2011)
Background: Orbital tuberculosis is rare even in endemic areas. The disease may involve soft tissue, lacrimal gland, or the periosteum or bones of the orbital wall. Case: We present an Indian girl, who presented with a slowly growing left-sided superotemporal orbital mass, with no significant previous medical history. The swelling turned to an abscess and burst spontaneously giving rise to a discharging sinus. The discharge was negative for any organism on Gram and Giemsa staining. A tuberculin skin test was strongly positive. Incisional biopsy showed caseating granuloma and Langhan’s giant cells suggestive of tubercular aetiology. The patient responded well to tuberculous chemotherapy. Conclusion: Although tuberculous dacryoadenitis is a very rare manifestation of tuberculosis, still the possibility should be entertained in a slowly growing mass of the lacrimal gland, especially in developing countries where the prevalence of tuberculosis is high. Key words: Tuberculosis, lacrimal gland, histopathology DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5281 Nepal J Ophthalmol 2011; 3(2): 210-213